Endurance training, expression, and physiology of LDH, MCT1, and MCT4 in human skeletal muscle - Dubouchaud, H.; Butterfield, G. E.; Wolfel, E. E.; Bergman, B. C.; Brooks, G. A. (American Journal of Physiology, Endocrinology and Metabolism, 2000)
To evaluate the effects of endurance training on the expression of monocarboxylate transporters (MCT) in human vastus lateralis muscle, we compared the amounts of MCT1 and MCT4 in total muscle preparations (MU) and sarcolemma-enriched (SL) and mitochondria- enriched (MI) fractions before and after training. To determine if changes in muscle lactate release and oxidation were associated with training-induced changes inMCTexpression, we correlated band densities in Western blots to lactate kinetics determined in vivo. Nine weeks of leg cycle endurance training [75% peak oxygen consumption (VO2peak)] increased muscle citrate synthase activity (175%, P , 0.05) and percentage of type I myosin heavy chain (150%, P,0.05); percentage of MU lactate dehydrogenase-5 (M4) isozyme decreased (212%, P , 0.05). MCT1 was detected in SL and MI fractions, and MCT4 was localized to the SL. Muscle MCT1 contents were consistent among subjects both before and after training; in contrast, MCT4 contents showed large interindividual variations. MCT1 amounts significantly increased in MU, SL, and MI after training (190%, 160%, and 178%, respectively), whereas SL but not MU MCT4 content increased after training (147%, P , 0.05). Mitochondrial MCT1 content was negatively correlated to net leg lactate release at rest (r 5 20.85, P , 0.02). Sarcolemmal MCT1 and MCT4 contents correlated positively to net leg lactate release at 5 min of exercise at 65% V ÿ O2peak (r 5 0.76, P,0.03 and r50.86, P,0.01, respectively). Results support the conclusions that 1) endurance training increases expression of MCT1 in muscle because of insertion of MCT1 into both sarcolemmal and mitochondrial membranes, 2) training has variable effects on sarcolemmal MCT4, and 3) both MCT1 and MCT4 participate in the cell-cell lactate shuttle, whereas MCT1 facilitates operation of the intracellular lactate shuttle.